Preparation of CoFe2O4/SiO2 Nanocomposites at Low Temperatures Using Short Chain Diols - Thomas Dippong; Erika Andrea Levei; Oana Cadar (Journal of Chemistry)
The preparation of 70% CoFe2O4/30% SiO2 (wt%) nanocomposites by sol-gel method using three short chain diols (1,2-ethanediol, 1,3-propanediol, and 1,4-butanediol) as chelators was studied. The Fourier transformed infrared spectra and X-ray diffraction patterns were used to confirm the formation of nanocomposites. The X-ray diffraction analysis showed that the chain length of the carboxylates embedded in the silica matrix influences the formation of crystallized cobalt ferrite as single phase at low temperatures. The influence of the methylene groups number in the precursors and annealing temperature on the nanocrystallite size was revealed. The stability of the obtained compounds was determined by calculation of thermodynamic parameters.